Evaluation of the Implementation of the Local Exhaust Ventilation System in the Testing Laboratory - Yudha Andaka Setyawan; Shintia Yunita Arini; Sri Widodo (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: One of the ways to control hazards with an engineering approach in an effort to reduce hazards due to chemical reactions in the laboratory is to install a ventilation system, especially in the Atomic Absorption Spectrophotometer (AAS). The research objectives of this study are to evaluate the implementation of the Local Exhaust Ventilation System in the AAS room. Method: This study used a descriptive observational method with a cross-sectional approach. It was carried out at the Testing Laboratory of the Technical Implementation Unit (henceforth-UPT) of Occupational Safety Surabaya. Data collection was carried out through direct observation in the field to determine the LEV system components and to measure the flow velocity in the inlet and outlet areas of the LEV system. The data obtained were analyzed descriptively by describing the situation systematically and factually. The data were then presented in the form of narration, tabulation, and figures. Results: The conditions of the Local Exhaust Ventilation (LEV), in terms of the design, type and material of each component such as the hood, ducting system and pump machine as well as the fan, are already in accordance with the tool specifications and ASHRAE standards. However, the LEV system has not installed an air cleaner. The results of the measurement show that flow velocity in the LEV system has met the standard, which is 10 m/s with the danger of fume contaminants. In fact, its volumetric flow rate has decreased by more than 20%. Conclusion: laboratory management is advised to consider installing an air cleaner on the LEV system installed in the Hitachi AAS so that contaminants released in the air are cleaner and more environmentally friendly.Keywords: hazard control, laboratory, local exhaust ventilation, ventilation